Risk assessment for major adverse cardiovascular events after noncardiac surgery using self-reported functional capacity: international prospective cohort study - Lurati Buse, Giovanna; Mauermann, Eckhard; Ionescu, Daniela; Szczeklik, Wojciech; De Hert, Stefan; Filipovic, Miodrag; Beck-Schimmer, Beatrice; Spadaro, Savino; Matute, Purificación; Bolliger, Daniel; Turhan, Sanem Cakar; van Waes, Judith; et al. (British journal of anaesthesia, 2023)
Background - Guidelines endorse self-reported functional capacity for preoperative cardiovascular assessment, although evidence for its predictive value is inconsistent. We hypothesised that self-reported effort tolerance improves prediction of major adverse cardiovascular events (MACEs) after noncardiac surgery. - Methods - This is an international prospective cohort study (June 2017 to April 2020) in patients undergoing elective noncardiac surgery at elevated cardiovascular risk. Exposures were (i) questionnaire-estimated effort tolerance in metabolic equivalents (METs), (ii) number of floors climbed without resting, (iii) self-perceived cardiopulmonary fitness compared with peers, and (iv) level of regularly performed physical activity. The primary endpoint was in-hospital MACE consisting of cardiovascular mortality, non-fatal cardiac arrest, acute myocardial infarction, stroke, and congestive heart failure requiring transfer to a higher unit of care or resulting in a prolongation of stay on ICU/intermediate care (≥24 h). Mixed-effects logistic regression models were calculated. - Results - In this study, 274 (1.8%) of 15 406 patients experienced MACE. Loss of follow-up was 2%. All self-reported functional capacity measures were independently associated with MACE but did not improve discrimination (area under the curve of receiver operating characteristic [ROC AUC]) over an internal clinical risk model (ROC AUCbaseline 0.74 [0.71-0.77], ROC AUCbaseline+4METs 0.74 [0.71-0.77], ROC AUCbaseline+floors climbed 0.75 [0.71-0.78], AUCbaseline+fitness vs peers 0.74 [0.71-0.77], and AUCbaseline+physical activity 0.75 [0.72-0.78]). - Conclusions - Assessment of self-reported functional capacity expressed in METs or using the other measures assessed here did not improve prognostic accuracy compared with clinical risk factors. Caution is needed in the use of self-reported functional capacity to guide clinical decisions resulting from risk assessment in patients undergoing noncardiac surgery. - Clinical trial registration - NCT03016936.